ON THE PECULIARITIES OF FORMING COMPLEX PROPOSALS BY MEANS OF SUFFIXES -sa, -se IN TURKISH LANGUAGE - Ismailova, L.M (LLC (EOOD) "SCIENTIFIC CHRONOGRAPH", 2019)
In modern Turkish linguistics, the attitude to complex sentences with a subordinate condition is different. Some linguists attribute this type of sentence to complex sentences, while some to simple ones. The reason for this is that the verb in the subordinate clauses of compound sentences formed by the suffixes -sa, -se is not evaluative. In connection with this problem, the article separately analyzes the opinion of a number of researchers. A comparative analysis of the category of conventions in different Turkic languages is carried out, examples are given, including from ancient Turkic language monuments. It is concluded that the form of a complex sentence with a subordinate clause was used in ancient languages, which is recorded in the Orkhon-Yenisei monuments, in ancient Uigur and other languages. At the same time, it should be noted that most researchers are inclined to think that in modern Turkish the conditional modality is inherent in participles, participles and the indefinite form of the verb. The article substantiates the idea that complex sentences with a subordinate clause of a condition exist in Turkish.